2021
DOI: 10.3389/fphys.2020.617374
|View full text |Cite
|
Sign up to set email alerts
|

The ECG Characteristics of Patients With Isolated Hypomagnesemia

Abstract: BackgroundElectrocardiographic (ECG) characteristics of patients with isolated hypomagnesemia are not well defined. We aimed to investigate these ECG characteristics in order to define clearly the features of isolated hypomagnesemia.HypothesisLower serum magnesium could affect ECG parameters after excluding potential confounders.MethodsThis retrospective study was of patients with low serum magnesium <0.65 mmol/L compared with the same patients after restoration to normal serum magnesium. Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…Patients with lower serum magnesium concentrations (≤1.9 mg/dL) have a higher risk of developing atrial fibrillation compared to those with magnesium levels in the upper normal limit. 150 , 151 …”
Section: Ecg Features In Electrolyte Disturbancesmentioning
confidence: 99%
“…Patients with lower serum magnesium concentrations (≤1.9 mg/dL) have a higher risk of developing atrial fibrillation compared to those with magnesium levels in the upper normal limit. 150 , 151 …”
Section: Ecg Features In Electrolyte Disturbancesmentioning
confidence: 99%
“…Changes in the surface electrocardiograms (ECG) associated with hypomagnesemia have been described over time, dependent and varying according to magnesium levels: ST segment depression, peaked and tall or flattened T waves, shortening of the PR interval and QTc, lowering of the QRS voltage, increasing in the QRS duration and the presence of U waves. In a study by Yang et al, isolated hypomagnesemia was found to be associated with increased dispersion of ventricular repolarization evaluated by Tpe /QT ratio (T peak-to-end interval (Tpe), QT-peak interval standard measurement from the beginning of the QRS complex to the peak of the T-wave (QTp)) [ 24 ].…”
Section: Cardiovascular Importance Of Magnesiummentioning
confidence: 99%
“…Patients with isolated hypomagnesemia (without other electrolyte disturbance) frequently present electrocardiogram disturbances with a P wave, corrected QT, and corrected T peak-to-endinterval duration prolonged, suggesting atrial depolarization and ventricular repolarization dispersion increased [176]. Even though the electrophysiologic action on cellular function is unclear, it suggests that these disturbances may have importance in the relationship between hypomagnesemia and sudden death [176]. Mg 2+ deficiency has been implicated in sudden death, and it is suspected that the electrophysiological changes induced by calcium are involved [177,178].…”
Section: Mg 2+mentioning
confidence: 99%